Literatur Riview terhadap Turnover Intention: Pengaruh Kepuasan Kerja dan Stres Kerja - nanda hanifah putri (Studi Ilmu Manajemen dan Organisasi, 2023)
Purpose: This study aims to determine the effect of Job Satisfaction and Job Stress on Employee Turnover Intention. Research Methodology: This study uses "Literature Review" which uses Google Scholar to collect data from online journal article literature. Results: The results of this study show that Job Satisfaction and Job Stress have a significant effect on Turnover Intention. Limitations: This research was only conducted for employees in one company. These variables include Job Satisfaction and Job Stress to see their effect on Turnover Intention. Contribution: The researcher hopes that this research will be able to provide management with an overview of what conditions occur in the company, and hope to provide insight into managing the company and creating a good working atmosphere so that it can affect Employee Turnover Intention.